Measurement of blue water footprint in Universidad Nacional in Costa Rica from 2012 to 2016 - Chavarría-Solera, Fabián; Gamboa-Venegas, Rebeca; Rodríguez-Flores, Jeison; Chinchilla-González, Diana; Herrera-Araya, Andrea; Herra-Solís, Ana Carolina (Uniciencia, 2020)
Quantifying and measuring the water footprint allows for the analysis and control over the environmental management of the institution and helps integrate college population, thus directing all efforts towards a sustainable development. The objective of this research is to quantify and calculate the institutional blue water footprint for the 2012-2016 period to analyze and compare its behavior over time, according to the variables included in the calculation such as consumption of water, fossil fuel, reams of paper and electrical energy (since they are important for the function and performance of institutional activities). The methodology applied was the one described by Hoekstra and Chapagain in the Water Footprint Assessment Manual, as well as the water footprint and virtual water factors taken from the Water Footprint Network. The corresponding amount was obtained for each item.  As a result, between 2012 and 2015, the Institutional Water Footprint decreased 8%, from 966 432 m3 to 888 693 m3, while in 2016 it slightly increased to 891 976 m3